PENGEMBANGAN TAMAN WISATA GROJOGAN SEWU SEBAGAI KAWASAN EKOWISATADI KABUPATEN KARANGANYAR - Suratno, - (2009)
The Title of this examination is "Pengembangan Taman Wisata Grojogan Sewu Sebagai Kawasan Ekowisata di Kabupaten Karanganyar." This title background comes from writer concerned and interest about the development that connectd to ecotourism. Now, this tourism activities is not just about bird observation, horse riding or track research into the forrest. But, it's more connected to forrest conservation concept and how to connect with local people in the area. In other words, ecotourism is a blend from so many interest from concerned about enuironment, social and economy. The thing also which wish to be developed at Taman Wisata Grojogan Sewu. Its the purpose is identification Taman Wisata Grojogan Sewu as area ecotorism facility analysis that is is supporting expansion as area ecotorism, identification of participation of public around in expansion as area ecotorism and analysis form of promotion which has been done by Taman Wisata Grojogan Sewu. Various data and information Taman Wisata Grojogan Sewu becoming this research focus obtained through field study and interview. Method applied is descriptive at qualitative approach by using analysis SWOT/TOWS. Analysis SWOT is apply matrix Internal Factor Evaluation ( IFE) and matrix Eksternal Factor Evaluation ( EFE). While matrix TOWS ( Threat, Opportunity, Weakness, and Strength) be strategy SO, WO, ST, and WT, which will yield Asumsi Kesimpulan Analisis Faktor Internal ( KAFI) and Kesimpulan Analisis Faktor Eksternal ( KAFE). Population is all area Taman Wisata Grojogan Sewu. Sample which in taking is number of tourists as tourist analysis. Development of Taman Wisata Grojogan Sewu as ecotourism area, Where all attractions and fascination tourism most of being based on nature. Potency owned not all can be implementation to be an ecotourism area. Some parts remain to be mass tourism area but is side is other still have farm as expansion of ecotourism area. Development of area ecotourism Grojogan Sewu is applied a zonation pattern that is Core Zone, Buffer Zone and Service Zone